Sistema de ejercicio para el desarrollo de las capacidades físicas en estudiantes de tercero de bachillerato de la Unidad Educativa “Abdón Calderón Muñoz”. - Ruiz Ortega, Reynaldo David (2025)
The development of physical abilities is essential for students, particularly during the final stages of adolescence. This study focuses on developing an exercise system for developing physical abilities among third-year high school students at the "Abdón Calderón Muñoz" Educational Unit, Babahoyo, Los Ríos, from October 2024 to March 2025. This research adopted a mixed-methods approach, combining qualitative and quantitative elements, as well as descriptive, action, and quasi-experimental research. Objective measurements of students' physical abilities were conducted, along with surveys and interviews to achieve a comprehensive approach. This study provides a precise perspective on the effect of a physical activity program on improving physical abilities among third-year high school students at the "Abdón Calderón Muñoz" Educational Unit. It highlights the importance of incorporating properly planned physical education programs to directly benefit the student community and the school. In addition, conclusions and practical suggestions are provided to optimize physical education instruction at this and similar schools. The purpose of these conclusions and recommendations is to promote an environment conducive to the development of students' physical skills.